POSITIVISTIC EFFECT OF THE CLASSICAL MUSIC COMBINED WITH STIMULATION, DETECTION, AND EARLY INTERVENTION (SDIDTK) ON CHILDREN'S GROWTH AND DEVELOPMENT - Sumaningsih, Rahayu; Sulikah, Sulikah; Fatimah, Fatimah; Santosa, Budi Joko (Universitas Aisyah Pringsewu, 2023)
According to several studies, music and stimuli provide a sense of security, comfort, and fun, including for children’s growth and development. The purpose of this study was to analyze the positive impact of the combination of classical music and stimulation, detection, and early intervention of growth and development (SDIDTK) on the growth and development of children. The method used in this study was a quasi-experimental design with a pretest-posttest with a control group. The two intervention groups were given a combination of natural and music therapy and SDIDTK, each intervention was given for 30 minutes and lasted for three consecutive days. A sample of 60 people was divided into two groups, namely children with classical music and SDIDTK as the treatment and the control groups. The dependent variable is classical music and SDIDTK and the independent variable is children without music and SDIDTK. Data analysis using t-test statistics. Results of the study of body weight before and after intervention show shows the p-value (0.000) alpha (0.005), so there is a significant difference in the averages of head circumference before and after the intervention. While head circumference averages before and after intervention show all three groups are below 0.05, meaning that the p values (0.009, 0.000, and 0.008) alpha (0.05), so there is a significant difference in average body weight before and after the intervention. The conclusion of this study recommends the use of classical-natural music therapy in combination with SDIDTK for a positive influence on children's growth and development.